An improved methodology to compute surface site interaction points using high density molecular electrostatic potential surfaces. Issue 28 (23rd October 2018) - Oliver, Antoni; Hunter, Christopher A; Prohens, Rafel; Rosselló, Josep Lluis
Abstract : The theoretical calculation of Surface Site Interaction Points (SSIP) has been used successfully in some applications in the solid and liquid phase. In this work we propose a new set of optimizations for the search of SSIP using the Molecular Electrostatic Potential Surfaces (MEPS) calculated with Density Functional Theory and B3LYP/6‐31*G basis set. The measures that have been implemented are based on the search for the best agreement between experimental H‐bond donor and acceptor parameters ( α and β ) and the MEPS extremes exploring a range of electron density levels. Additionally, a parameterization as a function of atom types has been performed. The results show that the MEPS calculated at 0.01 au electron density level slightly improves the correlation with experimental data in comparison with the calculation over other density values. This fact is related to the bigger contribution of local electrostatics at higher density levels. The refinement has provided significant improvements to the correlation between theoretical and experimental data. Moreover, the proposed calculation over 0.01 au is six times faster on average than the computation at 0.002 au. The proposed methodology has been developed with the purpose to obtain high precision SSIP in a fast way and to improve their applications in virtual cocrystal screening, calculation of free energies in solution and molecular docking. © 2018 Wiley Periodicals, Inc. Abstract : A method for fast and precise calculation of surface site interaction points (SSIP) has been proposed in this work. The basis of this method is the application of the footprint algorithm over high density molecular electrostatic potential surfaces (MEPS) calculated using DFT theory. Additionally, a parameterization of the MEPS as a function of atomic types has been performed. The methodology implies a better correlation of experimental data with ab‐initio calculations. This leads to better estimation of the intensity of H‐bond donor and acceptors and could produce significant improvements on SSIP applications.